Land Use Effects on Soil Quality Indicators: A Case Study of Abo-Wonsho Southern Ethiopia - Awdenegest Moges; Melku Dagnachew; Fantaw Yimer (Applied and Environmental Soil Science)
Soil quality assessment is valuable for evaluating agroecosystem sustainability, soil degradation, and identifying sustainable land management practices. This study compared soil quality within culturally protected forest areas and adjacent grassland, grazing land, and farmland in Abo-Wonsho, Southern Ethiopia. A total of 40 soil samples (4 land uses × 5 replications × 2 soil depth layers: 0 to 10 cm and 10 to 20 cm) were collected for analysis. Soil textural fractions (i.e., sand, silt, and clay percentage) varied with land use and soil depths even though the textural class across all land use types was sandy loam. Bulk density, soil organic carbon (SOC), and available potassium (K) varied significantly: , , and , respectively, with land use and soil depth, but other indicators showed no significant difference. We conclude soil quality can be protected and maintained by improving existing land use practices within both agricultural and modern forest management areas.